Fiqih Zakat: Tinjauan Hukum tentang Zakat atas Harta yang Diperoleh dari Usaha Haram - khoir, Abal; Julita, Elga Dwi; Wardana, Dimas Arya; Yulfina, Harmita; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Zakat is one of the important pillars of Islam, but there are still many questions about zakat on property obtained from haram businesses. This article aims to analyze the ruling of zakat on property obtained from haram business from the perspective of Islamic fiqh. The results of the study show that zakat on property obtained from haram businesses is not allowed because it does not meet the requirements of zakat. This research uses a literature research method by analyzing classical and contemporary fiqh books. The results of this research can help Muslims understand the law of zakat on property obtained from haram business and ensure that the property obtained in a halal way.